Torque Ripple Analysis of Double Rotor Eccentric Shell Rotating Multi-Speed Motor with Equal Width Curve - Guoqiang Zhao; Shitong Ren; Zhixin Wang; Junhua Lu; Zi Yang; Yongjie Xing (Innovation in Science and Technology, 2022)
With the rapid development of hydraulic technology, the type and performance of hydraulic motor are put forward higher requirements. In the actual working condition, the motor needs to have more than one stable torque and torque output, but the existing motor cannot be realized. In order to solve this problem, a series of new hydraulic motors based on double rotor structure are developed, thus further developing the multi-speed motor with equal width curve double rotor eccentric shell. One stator and two rotors cooperate with each other and enter through different inputs. The connection of the oil outlet can output a variety of different speed and torque, which realizes the function that multiple motors work synchronously and independently of each other in one shell. This paper mainly introduces the structural characteristics and working principle of the motor, and deduces the instantaneous torque and torque pulsation coefficient of the motor when working alone and in combination. At the same time, in order to understand the torque pulsation law of the internal and external motor more intuitively, the torque of the motor is analyzed and verified by Matlab software. It is concluded that the motor can realize many different speed and torque analysis. At the same time, through the analysis of instantaneous torque and torque pulsation coefficient, it can be concluded that the variation law of instantaneous torque output of internal and external motor combination is the best and the torque fluctuation is the smallest compared with that of internal and external motor alone.